A patient safety toolkit for family practices - Campbell, Stephen M.; Bell, Brian G.; Marsden, Katherine; Spencer, Rachel; Kadam, Umesh; Perryman, Katherine; Rodgers, Sarah; Litchfield, Ian; Reeves, David; Chuter, Antony; Doos, Lucy; Ricci-Cabello, Ignacio; et al. (Wolters Kluwer, 2018)
Objectives: Major gaps remain in our understanding of primary care patient safety. We describe a toolkit for measuring patient safety in family practices.